HEMOGRAM CONTROL IN POSTKOVID SYNDROME IN PREGNANT WOMEN OF DIFFERENT STAGES (World Bulletin of Public Health, 2022)
The health of pregnant women is one of the most urgent medical and social problems not only in Uzbekistan, but throughout the world. In 2021, the incidence of Covid-19 among pregnant women worldwide was 3,500,000, and the number of deaths was 12,300. (worldometer.info). Methods. Clinical material for the study was obtained from the data of general blood tests of 26 pregnant women who were treated with post-covid syndrome in the department of pathology of pregnant women of the Multidisciplinary Clinic of the Tashkent Medical Academy in 2021. The age of the patients is 19–39 years, the mean age is 26.59 ± 1.62 years. We studied the amount of hemoglobin in the general blood test, the total number of red blood cells. Results. Pregnant women were divided into 3 groups depending on the stage of fetal development. In patients, the level of hemoglobin, the total number of erythrocytes, platelets and leukocytes, and the erythrocyte sedimentation rate were determined. Conclusion. Thus, the depletion of hemoglobin and red blood cells was several times higher in pregnant women with severe Covid19 than in those who did not have it. In summary, the largest proportion of pregnant patients aged 19-25 years. Group II, the second trimester of pregnancy, was reported in 46% of patients. In terms of hemoglobin and erythrocyte counts, moderate anemia was detected in 61,34 of patients with thrombocytopenia in 42%.
Keywords: Pregnancy; Coronavirus; Anemia; Complications